Comparison of Multiple Stereoscopic and Monoscopic Digital Image Formats to Film for Diabetic Macular Edema Evaluation (2010)
ABSTRACT: Purpose.: To assess agreement between evaluations of monoscopic and stereoscopic digital images versus stereo film photographs in diabetic macular edema (DME). Methods : A 152-eye group of digital monoscopic macular images (seven-field sets and wide-angle mosaics) were compared with digital stereoscopic images (uncompressed and compressed seven-field sets) and stereo 35-mm film photos (Early Treatment Diabetic Retinopathy Study protocol) for the presence of hard exudates (HE), retinal thickening (RT), clinically significant macular edema (CSME), and RT at the center of the macular (RTCM). Results.: Agreement, according to the κ statistic, was almost perfect in identifying HE and RT between all digital formats and stereo film (HE, κ = 0.81–0.87; RT, κ = 0.87–0.92). Distribution in all digital formats was not significantly different from that in film (Bhapkar test: HE, P = 0.20–0.40; RT, P = 0.06–1.0). CSME and RTCM grading differences were either significant or trended toward significance. The readers detected CSME and RTCM in film images more often than in digital formats. In identifying DME features, agreement between evaluations of monoscopic digital formats and film was similar to that between stereo digital formats and film, and the performance of uncompressed images versus film was similar to that of compressed images versus film. Repeatability between readers was similar in evaluations of film and all digital formats. Repeatability in identifying RTCM was lower than that of other DME components in film and all digital formats. Conclusions.: Stereoscopic digital formats are equivalent to monoscopic for DME evaluation, but digital photography is not as sensitive as film in detecting CSME and RTCM.